Genesis 38 binne die Josefverhaal: "n Literêr-sosiologiese perspektief - Viljoen, D. A. (HTS teologiese studies, 2002)
The placing of Genesis 38 within the Joseph narrative: A literary sociological perspectiveA review of research on Gen 38 defines it as a literary riddle. The reasoning of this passage’s positioning and function within the Joseph narrative leads to a maze of different viewpoints. This article systematizes research on Gen 38 into three basic viewpoints: [1] Gen 38 forms an intrinsic part of the Joseph narrative; [2] Gen 38 is an independent literary unit; [3] Gen 38 is dialectically related to the Joseph narrative. Gen 38 reflects a polemical Southern perspective of the Kingdom of Judah against a Northern perspective of the Kingdom of Israel. This viewpoint links up with the argument that Gen 38 should be seen as dialectically related to the Joseph narrative.